PENGARUH KEMAMPUAN SPASIAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI KELAS XII MAN 2 AGAM TAHUN PELAJARAN 2024/2025 - Sarah, Muthia; ., Isnaniah; ., Junaidi; ., Rusdi (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to determine whether there is a significant effect of spatial ability on student’s mathematical problem solving skills in class XII MAN 2 AGAM in the 2024/2025 school year. This type of research is an ex posst facto research with quantitative research methods until this study is 30% of each XII MAN 2 AGAM class so that 38 students are obtained. The data collections technique used in this study is a test on each variable. The results showed that the average score os spatial ability reached 78,03% in the high category and the average score of student’s math problem solving ability of 73,58% was in the good category based on the correlation coefficient value of 0,491 which showed a moderate relationship so that is was found that spatial ability had a significant effect on mathematical problem solving ability.